Pediatric Plastic Surgery Operating Room Block-Time Utilization: A Casualty of Illness. Issue 5 (9th July 2022) - Maliha, Samantha G.; Bruce, Madeleine K.; Anstadt, Erin A.; Roy, Eva; Pfaff, Miles J.; Goldstein, Jesse A.; Losee, Joseph E.
Abstract : Background: Optimizing operating room (OR) utilization is a critical component of health care system efficiency. The purpose of our study was to analyze the extent of OR cancellation and its effect on raw utilization of OR block time allotted to surgeons in the pediatric plastic surgery department. Methods: The authors retrospectively reviewed the cases of 4 plastic surgeons at a tertiary pediatric hospital between 2018 and 2019. Data collected included patient demographics, type of surgery, time of cancellation, reason for cancellation, length of surgery, and minutes of block time allotted to each surgeon per year. Percent of cases canceled, scheduled times lost, and block times lost were calculated. Results: Surgeons A, B, C, and D scheduled 170, 416, 305, and 474 cases, respectively. Overall, 7% of cases were canceled, 9.1% of scheduled time was lost, and a total of 5.1% of block time was lost due to cancellation. Patients of surgeon A and D were more likely to cancel due to reasons classified as ''other, '' including causes such as failure of nil per os or a family's last-minute decision to forego elective surgery (33.3% and 37.2%, respectively), whereas patients of surgeon B and C were more likely to cancel due to illness (67.9% and 36.4%, respectively). Conclusions: Cancellations negatively impact raw utilization times; if fewer cases are performed, allotted block times are redistributed. Communication with patients in the week prior to surgery may allow for earlier identification of likely cancellations. Future directions include exploring whether particular surgeon characteristics are linked to rate of cancellations.